Flavonoids and amides from Melodorum fruticosum L. stem bark and their a-glucosidase inhibitory activity - Nguyen, Thi My Huong; Do, Thi My Lien (Vietnam Journal of Science and Technology, 2025)
Melodorum fruticosum Lour. (Annonaceae), a small tree or climber, is widely distributed in Central and Southern Vietnam. The leaves of M. fruticosum L. have been used as fork remedies for the treatment of digestive diseases and swelling of the breast, the roots of the plant were used to treat abdominal dyspepsia in women after giving birth. The dried powder of the stem of M. fruticosum L. collected in Lam Dong province was extracted with ethanol at room temperature and evaporated in the reduced pressure to yield an ethanol crude residue. From ethyl acetate extract, six compounds including eriodictyol (1), taxifolin (2), quercetin (3), paprazine (4), N-trans-caffeoyltyramine (5), and N-trans-feruloyltyramine (6) were isolated. The structures of these compounds were elucidated by NMR and ESI-MS as well as compared with data in the literatures. All isolated compounds, n-hexane, ethyl acetate and ethanol extracts were evaluated for their in vitro α-glucosidase inhibition, with acarbose as a positive control.